Pancreatic Perfusion CT in Early Stage of Severe Acute Pancreatitis - Yoshihisa Tsuji; Naoki Takahashi; Chiba Tsutomu (International Journal of Inflammation)
Early intensive care for severe acute pancreatitis is essential for improving SAP mortality rates. However, intensive therapies for SAP are often delayed because there is no ideal way to accurately evaluate severity in the early stages. Currently, perfusion CT has been shown useful to predict prognosis of SAP in the early stage. In this presented paper, we would like to review the clinical usefulness and limitations of perfusion CT for evaluation of local and systemic complications in early stage of SAP.